Biomechanical analysis of the support in race walking. Relationship between footprint, subtalar joint angles, and plantar pressures - J.L.L. Elvira; F.J. Vera-García; M. Meana; J.A. García (Asociación Española de Ciencias del Deporte, 2010)
The aims were to describe the behavior of the subtalar joint and foot in the race walk, and seek for correlations between them and the footprint. 12 race walkers participated in the study. The arch index was calculated on their footprints. Plantar pressures were measured and 3D photogrammetry used on a single support while they race walked at their own competitive speed. Maximum pressures were calculated in each region of the foot and also the maximum and minimum values of the three angles that describe the subtalar joint. The maximum pronation was higher than that described in the walking gait and similar to that of the running gait (-13.6 ± 3.90). In the beginning of the support the subtalar joint was between the walking and the running gaits. This suggests that the cushioning mechanism of this joint is adjusted according to the type of locomotion. The region of the foot that registered higher pressures was the external rearfoot (21.02 kPa/kg) followed by the internal forefoot (13.12 kPa/kg), showing a different behaviour to that of the running gait, in which both present similar maximum pressures. The subjects with lower arches tended to support with the internal face of the foot (r=-0.713) and with the leg inclined medially (r=0.874). Likewise, the racewalkers with higher arches registered higher pressures in the external part of the rearfoot, whereas the lowest ones did it in the internal part of the midfoot. Key Words: Biomechanics, race walk, footprint, subtalar joint, plantar pressure.